RECENT RESEARCH ON THE PERCEPTION OF THE TRANSLATING PROFESSION - Łomzik, Magdalena (Comparative Legilinguistics, 2021)
This article presents the latest research on the perception of the translating profession from the book Tłumacz oczami społeczeństwa edited by Katarzyna Liber-Kwiecińska. The reviewed monograph includes articles that complement current research on the perception of the role and work of interpreters. The presentation of an introductory article concerning the identity of a court interpreter is followed by the results of the work conducted by six teams of young scientists; these studies can be divided into three groups. The former relates to the perception of the interpreter's role by attorneys ad litem, judges, and students of non-philologic faculties, and to the cooperation between interpreters and judges. The second group includes a study on the required education of translators among students of philologic and non-philologic faculties. Finally, the last group contains research on the impact of the level of knowledge of a foreign language and the age of probants on the perception of the translating profession and the impact of the presence of an interpreter on the attractiveness of statements.